An extended discontinuous deformation analysis for simulation of grouting reinforcement in a water-rich fractured rock tunnel - Jingyao Gao; Siyu Peng; Guangqi Chen; Hongyun Fan (Journal of Rock Mechanics and Geotechnical Engineering)
Grouting has been the most effective approach to mitigate water inrush disasters in underground engineering due to its ability to plug groundwater and enhance rock strength. Nevertheless, there is a lack of potent numerical tools for assessing the grouting effectiveness in water-rich fractured strata. In this study, the hydro-mechanical coupled discontinuous deformation analysis (HM-DDA) is inaugurally extended to simulate the grouting process in a water-rich discrete fracture network (DFN), including the slurry migration, fracture dilation, water plugging in a seepage field, and joint reinforcement after coagulation. To validate the capabilities of the developed method, several numerical examples are conducted incorporating the Newtonian fluid and Bingham slurry. The simulation results closely align with the analytical solutions. Additionally, a set of compression tests is conducted on the fresh and grouted rock specimens to verify the reinforcement method and calibrate the rational properties of reinforced joints. An engineering-scale model based on a real water inrush case of the Yonglian tunnel in a water-rich fractured zone has been established. The model demonstrates the effectiveness of grouting reinforcement in mitigating water inrush disaster. The results indicate that increased grouting pressure greatly affects the regulation of water outflow from the tunnel face and the prevention of rock detachment face after excavation.